Answer:
Explanation:
General Equation of SHM is given by
[tex]x=A\cos \omega t[/tex]
[tex]v=-A\omega \sin \omega t[/tex]
where x=position of particle
A=maximum Amplitude
[tex]\omega =[/tex]angular frequency
t=time
At any time Total Energy is the sum of kinetic Energy and Elastic potential Energy i.e. [tex]\frac{1}{2}kA^2[/tex]
where k=spring constant
Potential Energy is given by [tex]U=\frac{1}{2}kx^2[/tex]
also it is given that Potential Energy(U) is equal to Kinetic Energy(K)
Total Energy[tex]=K+U[/tex]
Total[tex]=2U=2\times \frac{1}{2}kx^2[/tex]
[tex]\frac{1}{2}kA^2=2\times \frac{1}{2}kx^2[/tex]
[tex]x=\pm \frac{A}{\sqrt{2}}[/tex]
at [tex]x=\frac{A}{\sqrt{2}}[/tex]
velocity is [tex]v=\frac{A\omega}{\sqrt{2}}[/tex]